LEADERSHIP OF THE REGENT ABDULLAH AZWAR ANAS IN DEVELOPING AND ADVANCING THE DISTRICT OF BANYUWANGI ERA 2010-2015 - Agus Mursidi; Hervina Nurullita; Nafiatur Rizki (International Jurnal of Education Schoolars, 2021)
Leadership is an important part of a government. Because a leader is influential as a figure of change to achieve a goal for the common interest. To achieve the goal of developing and advancing Banyuwangi Regency in the 2010-2015 era, Banyuwangi is led by Regent Abdullah Azwar Anas. The topics of the problem in this research are: (1) Regent Abdullah Azwar Anas's efforts in developing Banyuwangi Regency in the 2010-2015 era, (2) the progress that has been made by Regent Abdullah Azwar Anas in Banyuwangi in the field of education and tourism, (3) the impact of the success of the Regent's leadership Abdullah Azwar Anas on the economy and welfare of society. The method used in this research is historical with heuristic data collection techniques, source criticism, interpretation, and historiography. The theory used in analyzing this research isbehavior theories and Contingency Theories. The results of this study indicate that (1) Anas' effort in developing Banyuwangi Regency in the 2010-2015 era is to create a vision and mission so that goals and objectives for Banyuwangi Regency achievement can be structured properly, (2) the progress that has been obtained from the leadership of Regent Anas in the field education and tourism is an increasing achievement from the previous leadership, (3) the impact of success on the economy and welfare of the Banyuwangi people, can be seen from the declining poverty rate in Banyuwangi and the per capita income of the Banyuwangi community continues to increase.